(untitled) (Research, Society and Development, 2020)
The generation of waste by the agribusiness can be an environmental problem. Malt bagasse, originated in large quantities in beer production, corresponds to up to 85% of the residues generated in this process and has as its main destination animal feed or landfills. Due to its nutritional constitution, it can be used in the preparation of food for human consumption. In this sense, we sought to develop and evaluate breads made from malt residue from the production of Pilsen and Porter style beers. For this, the breads were produced using malt bagasse, following a previously determined formulation and subsequently evaluated in relation to the parameters of humidity, pH, ash, proteins, lipids, crude fiber and total carbohydrates. Still, the breads were analyzed sensorially, where the profile of the tasters was characterized, the preference among the elaborated products, the acceptance by hedonic scale and the purchase intention. As main results, the breads showed nutritionally important values, with attention to fibers, which ranged from 2.15 to 2.20% for Porter and Pilsen and proteins, from 9.31 to 11%, respectively. In the sensory analysis, there was no statistical difference in the preference assessment. The breads obtained average grades above 6 (I liked it slightly) for all the attributes evaluated and the purchase intention showed that 37% of the judges would buy both elaborated products. Thus, the preparation of bread from waste from the beer industry proved to be a promising option to give a more noble destination to this residue, in addition to being nutritionally positive.